Small-molecule inhibition of Lats kinases may promote Yap-dependent proliferation in postmitotic mammalian tissues - Nathaniel Kastan (Nature Portfolio, 2021)
Although Hippo signaling restricts regeneration in many mammalian organs, the pharmaceutical tools available to modulate the pathway have been limited. Here, the authors report a small molecule that may inhibit a key element in the Hippo cascade and may activate regenerative responses in several mammalian tissues.